Rancang Bangun Aplikasi E- Laundry Berbasis Website (Studi Kasus : Aquatic Laundry Palangka Raya) - Widiatry, Widiatry; Stevani, Elwina (Journal of Information Technology and Computer Science, 2022)
Aquatic Laundry Palangka Raya is an bussiness that engaged in laundry services which is provide various services such as a complete laundry (dry cleaning and ironing), wash and dry, and the ironing only. Based on the analysis conducted, it was found that the transaction system running at Aquatic Laundry Palangka Raya was not optimal and found problems such as accumulation of archives and reports, slow information flow, slow process of collecting data, and difficulty in reporting.The solution for these problems is implementaion of a website that can be accessed by the costumer anytime and anywhere. The systems was built by using waterfall method which is consist of analysis, design, implementation, and testing phase. The design phase was done by making the architectural design of application, DFD (Data Flow Diagram), ERD (Entity Relationship Diagram), and User Interface. The implementation process was done by using PhPMyAdmin database and VisualStudioCode programming language. Then the system that had been built was tested by using black-box testing.The test results show that the system has been built in accordance with the specified functional requirements. This research has deliver a laundry information system services that can be used for managing laundry service at Aquatic Laundry Palangka Raya.